Pulmonary involvement in patients presenting with extra-pulmonary tuberculosis: thinking beyond a normal chest x-ray - Herath S; Lewis C (CSIRO Publishing, 2014)
INTRODUCTION: Recognition of pulmonary involvement in extra-pulmonary tuberculosis (TB) may be an important public health issue, as smear-negative pulmonary TB is responsible for about 17% of new infections. Pulmonary TB can be present despite a normal chest x-ray (CXR), even in human immunodeficiency virus (HIV)-negative patients. In this retrospective clinical audit, we reviewed a case series of HIV-negative patients with extra-pulmonary tuberculosis to identify the proportion with concurrent pulmonary TB despite an unremarkable CXR. METHODS: Clinical notes, microbiology results and CXR reports were reviewed from consecutive patients treated at Auckland City Hospital for extra-pulmonary TB from January 2007 to July 2010. RESULTS: Of the sample of 103 patients with extra-pulmonary TB, the majority of patients were born in an Asian country (n=70; 68%). The commonest presentation of extra-pulmonary TB was lymphadenopathy (n=51; 50%), followed by pleural (n=24; 23%) and bone (n=6; 6%) disease. Extra-pulmonary TB was diagnosed by biopsy or excision of the extra-pulmonary site in the majority (n=74; 72%), and by sputum testing alone in 26 (25%). The majority had CXR abnormalities (n=76; 74%). In the group with a normal CXR (n=27), 55% (n=15) had sputum cultures performed. In total, 18% (n=5) of patients with extra-pulmonary TB and a normal CXR had pulmonary TB, of whom two were smear positive. DISCUSSION: In patients with extra-pulmonary TB, sputum testing should be considered to detect concurrent pulmonary TB even if a CXR is normal, especially in immunosuppressed or symptomatic patients. This may aid diagnosis and determine infectivity and consequent public health action.